2017
DOI: 10.1016/j.rbmo.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors influencing pregnancy rates after intrauterine insemination with frozen donor semen: a prospective cohort study

Abstract: The extent to which certain parameters can influence pregnancy rates after intrauterine insemination with frozen donor semen was examined prospectively. Between July 2011 and September 2015, 402 women received 1264 IUI cycles with frozen donor semen in a tertiary referral infertility centre. A case report form was used to collect data prospectively. The primary outcome measure was clinical pregnancy rate (CPR), confirmed by detection of a gestational sac and fetal heartbeat using ultrasonography at 7-8 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…A relationship between AID female age and pregnancy success was confirmed when the AID female age was categorized -The AID clinical pregnancy rate was 51.7% for women below 34 years of age, 38.1% for woman between 34 years and 40 years, and 23.8% for women above 40 years (p=0.010, Table 1). The negative impact of female age on AID outcome has been reported [De Brucker et al 2009;Ghuman et al 2016;Thijssen et al 2017] and was confirmed in the present study as an AID woman under 34 years of age was a good prognostic factor for AID clinical pregnancy.…”
Section: Prognostic Factors For Aid Clinical Pregnancysupporting
confidence: 87%
See 1 more Smart Citation
“…A relationship between AID female age and pregnancy success was confirmed when the AID female age was categorized -The AID clinical pregnancy rate was 51.7% for women below 34 years of age, 38.1% for woman between 34 years and 40 years, and 23.8% for women above 40 years (p=0.010, Table 1). The negative impact of female age on AID outcome has been reported [De Brucker et al 2009;Ghuman et al 2016;Thijssen et al 2017] and was confirmed in the present study as an AID woman under 34 years of age was a good prognostic factor for AID clinical pregnancy.…”
Section: Prognostic Factors For Aid Clinical Pregnancysupporting
confidence: 87%
“…As it is a retrospective multicenter study, some factors were not collected by certain centers and therefore were not analyzed in the present study. These factors were: male BMI [Anifandis et al 2013], female BMI [Thijssen et al 2017], and parity of the couple [Dinelli et al 2014]. The embryo quality was not properly addressed and therefore only preliminary observations could be presented in the statistical analysis.…”
Section: 0%mentioning
confidence: 99%
“…Furthermore, the outcome of this study indicates that the IUI success rate is almost low when the female BMI is abnormal (BMI is less than 20 or larger than 30) and as much as it changes to a normal range of about 25, the probability of pregnancy increases. This finding is mentioned in the previous studies, too [38]. Meanwhile, reducing pregnancy rate can be mitigated by increase in the female age [39].…”
Section: Discussionmentioning
confidence: 54%
“…[49][50][51] Only those sperm banks which also recruit sperm donors and utilize the frozen treatment units in donor insemination procedures (or perhaps IVF) have any reliable means of validating both their sperm processing and storage conditions, proving effectiveness by establishing an acceptable pregnancy rate. 42,[52][53][54] In not doing so, clinics are at risk from patients who find that their samples either fail to survive in storage or are of very poor quality. Patients may then have a valid complaint if the sperm bank cannot demonstrate a validated freeze/thaw procedure or indeed that samples stored within the same freezer and at the same time have survived in adequate number.…”
Section: Risk and The Quality Of Frozen-thawed Materialsmentioning
confidence: 99%